Nanoparticle type polycarboxylic acid slump retaining agent and preparation method thereof
By developing nanoparticle polycarboxylic acid slump protectors and using the hydrophobic structure of three-layer core-shell polymer nanoparticles, the problem of rapid slump loss in poor quality sand and gravel aggregate environments is solved, and the stable maintenance of concrete slump and the extension of slump retention time is achieved.
Patent Information
- Application Number
- CN202311078923.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
Currently, polycarboxylic acid slump retainers are difficult to effectively maintain concrete slump in the environment of inferior sand and gravel aggregates, resulting in rapid slump loss and cannot meet construction requirements.
A nanoparticle type polycarboxylic acid slump-retaining agent is developed, which is a three-layer core-shell polymer nanoparticles. It is prepared by semi-continuous seed emulsion polymerization method, and uses a polymer structure with enhanced hydrophobicity to delay the adsorption of carboxyl groups and improve the slump-retaining performance.
This nanoparticle polycarboxylic acid slump retainer can maintain the concrete slump stability within 4 to 8 hours, extends the working time by more than 2 hours, adapts to the environment of inferior materials such as machined sand, and significantly improves the slump retaining performance.
Smart Images

Figure BDA0004413613110000031 
Figure BDA0004413613110000041 
Figure BDA0004413613110000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete admixtures, in particular to a nano-particle type polycarboxylic acid slump-preventing agent capable of controlling the slump of concrete for a long time and a preparation method thereof. Technical Background
[0002] In modern concrete, chemical admixtures play a vital role and are hailed as the third major breakthrough in concrete technology after reinforced concrete and prestressed concrete. To date, it can be said that the most important technological advances in concrete technology have been achieved through the introduction of innovative admixtures, while cement production itself has matured and paid more attention to the utilization of waste to promote a circular economy.
[0003] There is no doubt that polycarboxylate water reducers are the core of current chemical admixture technology, first because they can improve the processability of building materials (which usually brings huge cost savings), and second because of their huge consumption. In terms of molecular structure, polycarboxylic acid is a comb-shaped polymer, which consists of a main chain rich in carboxylic acid groups and polyether side chains. The carboxylic acid groups on the main chain can be directional adsorbed on the surface of positively charged cement or cement hydrates, while the polyether side chains stretch in the solution to form a hydration layer to provide spatial repulsion to prevent cement agglomeration. Therefore, this structure gives polycarboxylic acid a strong ability to disperse cement particles.
[0004] Since the invention of polycarboxylic acid by Dr. T. Hirata of Japan Catalyst Company in 1981, its market has developed rapidly. At present, the global production of polycarboxylic acid has exceeded 10 million tons per year. New manufacturers continue to enter the market, and new polycarboxylic acid products with new structures based on existing technologies or customized according to local needs are constantly coming out.
[0005] Polycarboxylic acid superplasticizers can be divided into two categories. One is called polycarboxylic acid water reducer, which is generally prepared by free radical copolymerization of polyether monomers and unsaturated acids (such as acrylic acid, maleic anhydride). Its function is to provide initial water reduction and dispersion for concrete, and it also has a certain slump retention ability. The other is called polycarboxylic acid slump retainer. In addition to the raw monomers used for water reducers, unsaturated esters (such as hydroxyethyl acrylate and hydroxypropyl acrylate) are also added during its preparation process. Since esters can hydrolyze carboxyl groups in the alkaline environment of cement, slump retainers generally have weak initial dispersion ability, but can prolong the slump retention time of concrete. Due to poor initial dispersion, slump retainers are not used alone, but are used in combination with water reducers to better exert their performance.
[0006] Although polycarboxylic acid technology is changing with each passing day, with the changes in the concrete raw material market, some current technologies cannot meet some demanding technical challenges. A more prominent problem is that as domestic high-quality concrete raw materials are exhausted, the proportion of some inferior materials that were rarely used in the past has begun to increase, resulting in the problem of concrete slump being unable to be maintained. For example, it is expected that machine-made sand will occupy more than 50% of the national sand market in the next five years, but there will be a large amount of stone powder (mud) that is difficult to remove during the manufacturing process of machine-made sand. Compared with cement, these stone powders can absorb polycarboxylic acid molecules better, resulting in the polycarboxylic acid molecules that could have provided slump retention being ineffectively adsorbed by the stone powder, and the concrete slump is lost rapidly, making it difficult to meet construction requirements.
[0007] The above problems cannot be solved by simply optimizing the ratio of traditional polycarboxylic acid slump-preventing agents, because stone powder will always adsorb a large number of polymer molecules containing carboxyl groups. Therefore, it is necessary to develop a new type of polycarboxylic acid slump-preventing agent, which introduces a protection mechanism in the traditional ester hydrolysis-carboxyl adsorption mechanism, so that the polycarboxylic acid molecules will not be ineffectively adsorbed in the early stage of hydration, so as to solve the problem of rapid slump loss of machine-made sand concrete encountered in actual projects. Summary of the invention
[0008] In view of the above technical problems, the present invention provides a nanoparticle-type polycarboxylic acid slump retaining agent, which has excellent slump retaining performance and can maintain the slump of concrete stable for 4 to 8 hours. Compared with general polycarboxylic acid slump retaining agents, it can extend the working time by more than 2 hours. It can solve the industry common problem of the general decrease in the slump retaining time of concrete caused by the deterioration of the quality of sand and gravel aggregates to a certain extent, and has bright application prospects in the current and future concrete admixture market.
[0009] The present invention provides a nanoparticle-type polycarboxylic acid slump-retaining agent, which is a polymer emulsion, wherein the polymer component is a three-layer core-shell polymer nanoparticle obtained by aqueous emulsion polymerization, and the actual solid content is 20-40wt%;
[0010] The polymer nanoparticle structure is composed of a core layer, an inner shell layer, and an outer shell layer from the inside to the outside, each layer is self-assembled by a corresponding polymer, and the outer layer can protect the inner layer; the constituent polymers of each layer independently have the following general structural formula (I), in which the four structural units of the polymer chain from left to right are formed by addition polymerization of a polyether monomer, an adsorption monomer, styrene, and a cross-linking monomer:
[0011]
[0012] Wherein, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, R3 is -H or C1-C4 alkane, R4 is -H or -COOH, EO, PO, BO refer to polyethylene oxide, polypropylene oxide and polybutylene oxide polymer segments respectively, EO, PO, BO are block or randomly distributed, X is other molecular structures in the cross-linking monomer except the carbon-carbon double bond, and the wavy line structure refers to other segments of the molecular structure shown in the general formula (I), indicating that the structure is a three-dimensional high molecular cross-linked polymer;
[0013] The cross-linking monomer structure contains at least two polymerizable double bonds and a hydrolyzable ester group;
[0014] The three-layer core-shell nanoparticles are prepared by semi-continuous seed emulsion polymerization. During the emulsion polymerization, the monomers used are polyether monomers, adsorption monomers, cross-linking monomers and styrene monomers.
[0015] The mass ratio of the raw material monomers polyether monomer A, adsorption monomer A, crosslinking monomer A, and styrene monomer used in the core layer is 75-90:10-25:1-3:1-2.5; the weight average molecular weight of the polyether monomer A is 3000-5000, and it contains EO and PO segments, and the mass ratio of EO and PO segments is 1:0.2-0.8, and the EO and PO segments can be distributed in blocks or randomly;
[0016] The mass ratio of the raw material monomers polyether monomer B, adsorption monomer B, crosslinking monomer B, and styrene monomer used in the inner shell layer is 75-90:10-25:2-5:2-4; the weight average molecular weight of polyether monomer B is 1000-4000, and it contains EO, PO, and BO segments, and the mass ratio of EO, PO, and BO segments is 1:0.3-1:0.05-0.2, and EO, PO, and BO segments can be distributed in blocks or randomly;
[0017] The mass ratio of the raw material monomers polyether monomer C, adsorption monomer C, crosslinking monomer C, and styrene monomer used in the outer shell layer is 75-90:10-25:2-8:3-5; the weight average molecular weight of the polyether monomer C is 1000-4000, and it contains EO, PO, and BO segments, and the mass ratio of EO, PO, and BO segments is 1:0.3-1:0.2-0.4, and the EO, PO, and BO segments can be distributed in blocks or randomly;
[0018] The solid content of the three-layer core-shell nanoparticles finally obtained is 20-40wt%, wherein the mass ratio of the core layer, the inner shell layer and the outer shell layer is 10-30:30-70:10-20 (the mass ratio is determined by the monomer feed amount in each step).
[0019] The particle size of the three-layer core-shell nanoparticles of the present invention is 40-80 nm. If the particle size is too small, the hydrolysis is too fast and it is difficult to fully exert the long-lasting collapse function. If the particle size is too large, the emulsion is unstable and easy to precipitate, which affects the use.
[0020] The three-layer core-shell nanoparticles of the present invention can be formed by polymerization self-assembly and can exist stably in water for a long time on the premise that the hydrophobicity of the constituent polymers of the core layer, inner shell layer and outer shell layer of the nanoparticles must be enhanced in sequence, so that the polymers can be deposited on the seeds formed by polymerization in sequence to form a multilayer structure, and cross-linking monomers are required to make the polymers body-shaped, so as to prevent the outer layer polymer from moving to the inner layer due to its strong hydrophobicity and causing phase inversion. The condition for judging the size of the hydrophobicity is that the greater the mass of the PO and BO segments in the polyether monomer, the ester in the adsorption monomer, the styrene monomer, and the cross-linking monomer, the stronger the hydrophobicity of the polymer.
[0021] The principle of the three-layer core-shell nanoparticles of the present invention to play a long-term collapse-preserving function is: after being added to the cement paste, due to the structure of the nanoparticles, its carboxyl group will not be adsorbed quickly, but will play a collapse-preserving role only after the outer layer structure is gradually destroyed by the alkaline environment of the cement. First, the outer layer hydrolyzes polycarboxylic acid to play a role in dispersing cement particles, while the inner layer structure will not be affected due to the barrier effect of the outer layer. As hydration proceeds, the early polycarboxylic acid molecules are covered by the hydration products and lose the dispersion effect. At this time, the outer layer structure has been digested, and the inner layer begins to hydrolyze polycarboxylic acid to be adsorbed on the surface of the cement hydration product, and continues to play a dispersion effect. Since this technology has a three-layer nanostructure, the outer layer can protect the inner layer, will not be ineffectively adsorbed quickly, and can be gradually hydrolyzed into polycarboxylic acid in three stages, so the collapse-preserving time is more durable than the primary hydrolysis of ordinary polycarboxylic acid.
[0022] The three-layer core-shell nanoparticles of the present invention are prepared by semi-continuous seed emulsion polymerization. Except for a small amount of monomers used for primer, most of the monomers are added by dropwise addition. The dropwise addition process keeps the reaction system in a "starved state" to prevent the newly formed polymer from being dispersed in the solution instead of accumulating on the already formed polymer nanoparticles (seeds). During the emulsion polymerization process, the monomers used are divided into four categories, namely polyether monomers, adsorption monomers, crosslinking monomers and styrene monomers.
[0023] The polyether monomer A, polyether monomer B and polyether monomer C are independently selected from addition products of unsaturated alcohols and alkylene oxides, and have the following general structural formula (II):
[0024]
[0025] Among them, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, EO, PO, and BO refer to polyethylene oxide, polypropylene oxide, and polybutylene oxide polymer chain segments, respectively, and EO, PO, and BO can be either block or randomly distributed.
[0026] The adsorption monomer A, adsorption monomer B and adsorption monomer C are independently selected from any two or more of acrylic acid, maleic anhydride, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate and tert-butyl acrylate, and mixed in any proportion, and the amount of acrylic acid and acrylate cannot be zero.
[0027] The polyether monomer and the adsorption monomer are raw material monomers commonly used in the synthesis of polycarboxylic acids. The polyether monomer is a side chain in the polycarboxylic acid structure. The acrylic acid (ester) monomer contains a carboxylic acid group or an ester group that can be hydrolyzed to a carboxylic acid group in an alkaline environment and is an adsorption component in the polycarboxylic acid structure.
[0028] The cross-linking monomer structure contains at least two polymerizable double bonds, which can cross-link the synthesized linear-comb polymer into a three-dimensional shape to facilitate the formation of stable nanoparticles. At the same time, the structure contains a hydrolyzable ester group, which can hydrolyze the three-dimensional polymer into a linear-comb shape of a common polycarboxylic acid in the alkaline environment of cement, thereby exerting a dispersing effect.
[0029] The crosslinking monomer A, crosslinking monomer B and crosslinking monomer C are independently selected from any one or more of ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, 1,6-ethylene glycol diacrylate, allyl acrylate and diallyl maleate.
[0030] The styrene monomer is a cheap hydrophobic monomer and can assist the synthesized polymer to self-assemble into nanoparticles in water.
[0031] The preparation method of the nanoparticle-type polycarboxylic acid collapse-preventing agent of the present invention can be specifically divided into the following three steps:
[0032] (1) Preparation of core layer: In a four-necked bottle equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, water, polyether monomer A, 30% of adsorption monomer A, crosslinking monomer A and styrene monomer are added to the four-necked bottle, and pre-emulsified by stirring and dispersing at a constant speed. After a stable emulsion is formed, the temperature is raised to 60-90° C., initiator I is added, and the remaining 70% of adsorption monomer A, crosslinking monomer A and styrene monomer are added dropwise for 1-2 hours. After the addition is completed, the reaction is kept warm for 0.5 hours to obtain a seed emulsion, which is the core layer of the three-layer core-shell nanoparticles.
[0033] (2) Preparation of the inner shell layer: Add polyether monomer B and initiator II to the core layer emulsion prepared in step (1), and dropwise add adsorption monomer B, crosslinking monomer B, and styrene monomer for 3 to 5 hours. After the dropwise addition is completed, heat-retaining reaction is performed for 0.5 hours to obtain a core-shell seed emulsion;
[0034] (3) Preparation of the outer shell layer: Add polyether monomer C and initiator III to the core-shell emulsion prepared in step (2), and dropwise add adsorption monomer C, crosslinking monomer C, and styrene monomer for 0.5 to 2 h. After the dropwise addition is completed, the reaction is kept warm for 0.5 h to obtain three-layer core-shell nanoparticles, which are the nanoparticle-type polycarboxylic acid collapse retaining agent of the present invention;
[0035] The amount of initiator I used in step (1) is 0.1 to 1.5 wt% of the total amount of the reaction monomers used in step (1);
[0036] The amount of initiator II used in step (2) is 0.1 to 1 wt% of the total amount of the reaction monomers used in step (2);
[0037] The amount of initiator III used in step (3) is 0.1 to 0.4 wt% of the total amount of the reaction monomers used in step (3);
[0038] The polyether monomer is used not only as a comonomer but also as an emulsifier in the reaction, so that the reaction is a soap-free emulsion polymerization. Therefore, the polyether monomer must have certain hydrophilicity and hydrophobicity, so the polyether monomer must contain an EO segment and at least one of the PO and BO segments.
[0039] The initiator I, initiator II and initiator III are independently selected from any one of ammonium persulfate, potassium persulfate, sodium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline and azobiscyanovaleric acid.
[0040] The nanoparticle polycarboxylic acid slump-preserving agent of the present invention has a dosage of 0.02% to 0.2% of the total mass of the gelling material, the dosage is the pure solid dosage, and the percentage is the mass percentage. Too low dosage will deteriorate its performance, and too high dosage will cause economic waste and fail to improve performance.
[0041] The nanoparticle-type polycarboxylic acid slump-preventing agent of the present invention can be mixed with other commercially available plasticizers, such as wood sulfonates, naphthalene sulfonates, polycarboxylates, etc., and can also be added with air entraining agents, retarders, early strength agents, expansion agents, viscosity enhancers, shrinkage reducers and defoamers before use.
[0042] The beneficial effects of the nanoparticle-type polycarboxylic acid collapse-preventing agent of the present invention are as follows:
[0043] (1) Good collapse protection performance, which can achieve a collapse protection time of more than 4 hours for concrete slump. When applied to actual projects, it can effectively reduce the dosage of collapse protection agent and save costs;
[0044] (2) It has low sensitivity to the mud content in sand and gravel aggregates and strong adaptability, making it particularly suitable for solving the problem of rapid loss of concrete slump caused by machine-made sand.
[0045] (3) The production process adopts a one-pot method, which allows continuous production in the same reactor. It is highly efficient, does not use organic solvents, is environmentally friendly, and is easy to achieve large-scale production. DETAILED DESCRIPTION
[0046] The following describes in more detail the preparation process of the nanoparticle-type polycarboxylic acid collapse-preventing agent of the present invention through examples. These examples are given in an illustrative manner, and their purpose is to allow people familiar with the technology to understand the content of the present invention and implement it accordingly, but these examples do not limit the scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.
[0047] In the embodiments of the present invention, except for the polyether monomer, the names and codes of the other raw materials used are shown in the following table.
[0048] Table 1 Raw material names and codes
[0049] name Code name Code acrylic acid AA Tripropylene glycol diacrylate TPGDA Maleic anhydride MAH Trimethylolpropane triacrylate TMPTA Methyl acrylate MA 1,6-Ethylene glycol diacrylate HDDA Ethyl acrylate EA Allyl acrylate AMA Propyl acrylate nPA Diallyl Maleate DAM Isopropyl acrylate iPA Styrene St Butyl acrylate nB Ammonium Persulfate APS Isobutyl acrylate iBA Potassium Persulfate KPS Tert-Butyl Acrylate tB Sodium Persulfate SPS Ethylene glycol diacrylate EGDA Azobisisobutylamidine hydrochloride V-50 Diethylene glycol diacrylate DEADA Isobutylene azodicarbonyl hydrochloride VA-044 Triethylene glycol diacrylate TEGDA Isobutylene azodiphenylamine VA-061 Dipropylene glycol diacrylate DPGDA Azobiscyanovaleric acid V-501
[0050] The solid content of the nanoparticles synthesized in the embodiment of the present invention was measured after drying the water in a high-temperature blast drying oven, and the particle size was tested by a dynamic light scattering instrument (DLS, ALV / CGS-3, Germany) with a test laser wavelength of 610 nm and a test angle of 90°.
[0051] Example 1
[0052] A method for preparing a nanoparticle-type polycarboxylic acid collapse-preventing agent can be specifically divided into the following three steps:
[0053] (1) Preparation of core layer: In a four-necked bottle equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, 2487.2 parts of water and 78.5 parts of a polyether monomer allyl polyoxyethylene-oxypropylene ether (code A-EO2600-PO900, A represents that the initiator used in the polyether is allyl alcohol, and the number represents the molecular weight of the chain segment, the same below) are added to the four-necked bottle, and then 3.6 parts of AA, 17.5 parts of MA, 2.7 parts of EGDA, 1. 8 parts of St were prepared into a solution, 30% of which was dripped into a four-necked flask within 30 minutes, and the stirrer was stirred at a speed of 300 r / min to disperse the base material evenly for pre-emulsification. After a stable emulsion was formed, the temperature was raised to 60°C, 1.51 parts of APS initiator were added, and the remaining monomer solution was dripped. The dripping time was 1 hour. After the dripping was completed, the reaction was kept warm for 0.5 hours to obtain a seed emulsion, which was the core layer of the three-layer core-shell nanoparticles;
[0054] (2) Preparation of the inner shell layer: 384.6 parts of polyether monomer A-EO1170-PO1080-BO150 and 0.62 parts of initiator APS were added to the core layer emulsion prepared in step (1), and a solution prepared by 9.4 parts of AA, 40.3 parts of nPA, 16.3 parts of TPGDA, and 11.3 parts of St was added dropwise for 3 hours. After the addition was completed, the reaction was kept warm for 0.5 hours to obtain a core-shell seed emulsion;
[0055] (3) Preparation of outer shell layer: 55.6 parts of polyether monomer T-EO1320-PO1170-BO520 and 0.09 parts of initiator APS were added to the core-shell emulsion prepared in step (2), and a solution prepared by 1.8 parts of MAH, 9.9 parts of MA, 2.9 parts of EGDA and 2.8 parts of St was added dropwise for 1 hour. After the addition was completed, the mixture was kept warm for 0.5 hours to obtain three-layer core-shell nanoparticles, which are the nanoparticle-type polycarboxylic acid collapse inhibitor of the present invention. The solid content was 20.5 wt % and the particle size was 45.0 nm as measured by DLS.
[0056] The synthesis methods of Examples 2 to 12 are consistent with those of Example 1, and the specific reaction conditions are listed in the following table. Tables 2, 3, and 4 are the types and amounts of the raw materials in steps 1, 2, and 3. Table 5 is the specific reaction temperature, dropwise addition time, solid content, product particle size, and other data in the examples.
[0057] Table 2 Raw materials and amounts used in step 1
[0058]
[0059]
[0060] Note: (1) The unit of quantity is parts by mass
[0061] (2) The first letter in the polyether type represents the unsaturated alcohol used as the initiator for preparing the polyether. A represents allyl alcohol, H represents methyl allyl alcohol, T represents isopentenyl alcohol, V represents diethylene glycol monovinyl ether, and HV represents 4-hydroxybutyl vinyl ether. The numbers represent the molecular weights of the EO, PO, and BO segments.
[0062] Table 3 Raw materials and amounts used in step 2
[0063]
[0064] Table 4 Raw materials and amounts used in step 3
[0065]
[0066]
[0067] Table 5 Reaction conditions and solid content, particle size test data
[0068]
[0069] In order to test the performance of the particle-type polycarboxylic acid slump retaining agent synthesized in the example, two samples of polycarboxylic acid slump retaining agents commonly found on the market were synthesized as comparative examples to serve as control samples for subsequent application examples.
[0070] Comparative Example 1
[0071] 240 parts of H-EO2330 oxyethylene ether, 1.2 parts of 30 wt% hydrogen peroxide and 240 parts of water were added to a four-necked flask equipped with a thermometer and a mechanical stirrer, and then stirred and heated to 40°C. At this temperature, a mixed solution consisting of 7.2 parts of AA, 34 parts of hydroxyethyl acrylate, 0.75 parts of mercaptopropionic acid, 0.29 parts of L-ascorbic acid and 42 parts of water was added dropwise for 2 hours. After the addition was completed, the temperature was kept for 2 hours. M was measured by gel permeation chromatography w The molecular weight distribution coefficient is 39800 and 1.77.
[0072] Comparative Example 2
[0073] 240 parts of T-EO2900 oxyethylene ether, 2.2 parts of 30 wt% hydrogen peroxide and 240 parts of water were added to a four-necked flask equipped with a thermometer and a mechanical stirrer, and then stirred and heated to 45°C. At this temperature, a mixed solution consisting of 12 parts of AA, 41 parts of hydroxypropyl acrylate, 0.62 parts of mercaptopropionic acid, 0.36 parts of L-ascorbic acid and 54 parts of water was added dropwise for 2 hours. After the addition was completed, the temperature was kept for 2 hours. M was measured by gel permeation chromatography w The molecular weight distribution coefficient is 50700 and 1.74.
[0074] Application Examples
[0075] Application Example 1
[0076] According to the provisions of GB / T8077-2000 "Test Method for Homogeneity of Concrete Admixtures", the polycarboxylic acid slump-retaining agent synthesized in the embodiments of the present invention and the comparative examples was subjected to mortar fluidity measurement to test its slump-retaining performance. Test ratio: cement 450, fly ash 120, mineral powder 80, river sand 1300, water 260, the dosage of the embodiment and comparative example slump-retaining agent was fixed at 0.08%, and 0.11% of ordinary polycarboxylic acid water-reducing agent was added to ensure appropriate initial fluidity. The mortar test data is shown in Table 6. It can be seen from the data in the table that under the same dosage and water-cement ratio, the initial fluidity of the embodiment and comparative example samples is within 170-190mm, indicating that there is no obvious difference in the water-reducing ability of the two, but in terms of slump-retaining, the comparative example has begun to lose fluidity within 2 to 3 hours, the fluidity is less than 200mm at 3 hours, and the fluidity has been lost at 4 hours. The examples can ensure that there is no loss in fluidity for 2 hours or even 3 hours, and the fluidity is greater than 240 mm at 4 hours, which shows that the nanoparticle-type polycarboxylic acid collapse-preventing agent synthesized in the examples of the present invention has a collapse-preventing ability far exceeding that of conventional polycarboxylic acid collapse-preventing agents.
[0077] Table 6 Cement mortar fluidity test results
[0078]
[0079]
[0080] Note: -- indicates loss of fluidity
[0081] Application Example 2
[0082] The river sand was replaced with machine-made sand to test the adaptability of the polycarboxylic acid slump-retaining agent synthesized in the embodiments and comparative examples of the present invention in machine-made sand. Test ratio: 400g cement, 100g fly ash, 50g mineral powder, 1250g machine-made sand, 240g water. The amount of slump-retaining agent in the embodiments and comparative examples was fixed at 0.13%. In addition, 0.15% of ordinary polycarboxylic acid water-reducing agent was added to ensure the appropriate initial fluidity. The mortar test data is shown in Table 7. As can be seen from the data in the table, the fluidity loss of the comparative samples is extremely fast. Both comparative examples 1 and 2 completely lose fluidity within 3 hours, indicating that machine-made sand does greatly accelerate the loss rate of cement slurry, and it is difficult for the existing slump-retaining agent to form effective control. However, the samples in the embodiments show very good slump-retaining advantages. All samples still maintain considerable fluidity (>200mm) at 4 hours, and the fluidity of some samples is still maintained above 240mm at 4 hours. Compared with the comparative example, the collapse time of the example sample can be extended by more than 2 hours, which indicates that the nanoparticle-type polycarboxylic acid collapse retaining agent synthesized in the example of the present invention can solve the problem of excessive loss of concrete fluidity caused by the large-scale promotion of machine-made sand at this stage.
[0083] Table 7 Test results of fluidity of machine-made sand mortar
[0084]
[0085]
[0086] Note: -- indicates loss of fluidity
[0087] Application Example 3:
[0088] Next, the performance of the polycarboxylic acid slump-retaining agent synthesized in the embodiments and comparative examples of the present invention in concrete was tested according to the method specified in GB8076-2008. Concrete mass mix ratio: cement 280, mineral powder 60, fly ash 60, machine-made sand 780, crushed stone 1100, water 168, the dosage of the embodiment and comparative example slump-retaining agent was fixed at 0.10%, and 0.12% of ordinary polycarboxylic acid water-reducing agent and 0.04% of sodium saccharide were added to ensure appropriate initial fluidity and coagulation performance. The concrete slump test data is shown in Table 8. It can be seen that, similar to the mortar results, the slump loss of the comparative example sample is extremely fast, while the loss rate of the embodiment sample is very slow. At 4h, the slump of the embodiment sample is generally above 20cm, with good construction performance. This shows that the nanoparticle-type polycarboxylic acid slump-retaining agent of the present invention can effectively control the slump loss rate of concrete, and the slump-retaining time can be extended to more than 4h.
[0089] Table 8 Slump test results of machine-made sand concrete
[0090]
[0091]
Claims
1. A nanoparticle-type polycarboxylic acid collapse-preventing agent, characterized in that: The polycarboxylic acid collapse-preserving agent is a polymer emulsion, the polymer component of which is a three-layer core-shell polymer nanoparticle obtained by aqueous emulsion polymerization, and the actual solid content is 20-40wt%; The polymer nanoparticle structure is composed of a core layer, an inner shell layer, and an outer shell layer from the inside to the outside, and each layer is self-assembled by a corresponding polymer. The constituent polymers of each layer independently have the following general structural formula (I), in which the four structural units of the polymer chain from left to right are formed by addition polymerization of a polyether monomer, an adsorption monomer, styrene, and a cross-linking monomer: Wherein, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, R3 is -H or C1-C4 alkane, R4 is -H or -COOH, EO, PO, BO refer to polyethylene oxide, polypropylene oxide and polybutylene oxide polymer segments respectively, EO, PO, BO are block or randomly distributed, X is other molecular structures in the cross-linking monomer except the carbon-carbon double bond, and the wavy line structure refers to other segments of the molecular structure shown in the general formula (I); the cross-linking monomer structure contains at least two polymerizable double bonds and a hydrolyzable ester group; The mass ratio of the raw material monomers polyether monomer A, adsorption monomer A, crosslinking monomer A, and styrene monomer used in the core layer is 75-90:10-25:1-3:1-2.5; the weight average molecular weight of the polyether monomer A is 3000-5000, and it contains EO and PO segments, and the mass ratio of EO and PO segments is 1:0.2-0.8, and the EO and PO segments can be distributed in blocks or randomly; The mass ratio of the raw material monomers polyether monomer B, adsorption monomer B, crosslinking monomer B, and styrene monomer used in the inner shell layer is 75-90:10-25:2-5:2-4; the weight average molecular weight of polyether monomer B is 1000-4000, and it contains EO, PO, and BO segments, and the mass ratio of EO, PO, and BO segments is 1:0.3-1:0.05-0.2, and EO, PO, and BO segments can be distributed in blocks or randomly; The mass ratio of the raw material monomers polyether monomer C, adsorption monomer C, crosslinking monomer C and styrene monomer used in the outer shell layer is 75-90:10-25:2-8:3-5; the weight average molecular weight of the polyether monomer C is 1000-4000, and it contains EO, PO and BO segments, the mass ratio of EO, PO and BO segments is 1:0.3-1:0.2-0.4, and the EO, PO and BO segments can be distributed in blocks or randomly.
2. A nanoparticle-type polycarboxylic acid collapse-preventing agent according to claim 1, characterized in that: The mass ratio of the core layer, the inner shell layer and the outer shell layer of the three-layer core-shell polymer nanoparticles is 10-30:30-70:10-20.
3. A nanoparticle-type polycarboxylic acid collapse-preventing agent according to claim 2, characterized in that: The particle size of the three-layer core-shell polymer nanoparticles is 40-80 nm.
4. A nanoparticle-type polycarboxylic acid collapse-preventing agent according to claim 3, characterized in that: The polyether monomer A, polyether monomer B and polyether monomer C are independently selected from addition products of unsaturated alcohols and alkylene oxides, and have the following general structural formula (II): Among them, R1 is -H or -CH3, R2 is -O-, -CH2O-, -CH2CH2O- or -OCH2CH2CH2CH2O-, EO, PO, and BO refer to polyethylene oxide, polypropylene oxide, and polybutylene oxide polymer chain segments, respectively, and EO, PO, and BO can be either block or randomly distributed.
5. The nanoparticle-type polycarboxylic acid collapse-preventing agent according to claim 3, characterized in that: The adsorption monomer A, adsorption monomer B and adsorption monomer C are independently selected from any two or more of acrylic acid, maleic anhydride, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate and tert-butyl acrylate, and mixed in any proportion, and the amount of acrylic acid and acrylate cannot be zero.
6. The nanoparticle-type polycarboxylic acid collapse-preventing agent according to claim 3, characterized in that: The crosslinking monomer A, crosslinking monomer B and crosslinking monomer C are independently selected from any one or more of ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, 1,6-ethylene glycol diacrylate, allyl acrylate and diallyl maleate.
7. The method for preparing a nanoparticle-type polycarboxylic acid collapse-preventing agent according to any one of claims 1 to 6, characterized in that: The specific steps are as follows: (1) Preparation of core layer: In a four-necked bottle equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube, water, polyether monomer A, 30% of adsorption monomer A, crosslinking monomer A and styrene monomer are added to the four-necked bottle, and pre-emulsified by stirring and dispersing at a constant speed. After a stable emulsion is formed, the temperature is raised to 60-90° C., initiator I is added, and the remaining 70% of adsorption monomer A, crosslinking monomer A and styrene monomer are added dropwise for 1-2 hours. After the addition is completed, the reaction is kept warm for 0.5 hours to obtain a seed emulsion, which is the core layer of the three-layer core-shell nanoparticles. (2) Preparation of the inner shell layer: Add polyether monomer B and initiator II to the core layer emulsion prepared in step (1), and dropwise add adsorption monomer B, crosslinking monomer B, and styrene monomer for 3 to 5 hours. After the dropwise addition is completed, heat-retaining reaction is performed for 0.5 hours to obtain a core-shell seed emulsion; (3) Preparation of the outer shell layer: Add polyether monomer C and initiator III to the core-shell emulsion prepared in step (2), and dropwise add adsorption monomer C, crosslinking monomer C, and styrene monomer for 0.5 to 2 h. After the dropwise addition is completed, keep the reaction warm for 0.5 h to obtain three-layer core-shell nanoparticles, namely the nanoparticle-type polycarboxylic acid collapse inhibitor.
8. The preparation method according to claim 7, characterized in that: The initiator I, initiator II, and initiator III are independently selected from any one of ammonium persulfate, potassium persulfate, sodium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline, and azobiscyanovaleric acid; The amount of initiator I used in step (1) is 0.1 to 1.5 wt% of the total amount of the reaction monomers used in step (1); The amount of initiator II used in step (2) is 0.1 to 1 wt% of the total amount of the reaction monomers used in step (2); The amount of initiator III used in step (3) is 0.1 to 0.4 wt % of the total amount of the reaction monomers used in step (3).
9. The method for using the nanoparticle-type polycarboxylic acid collapse-preventing agent according to any one of claims 1 to 6, characterized in that: The dosage of the nano-particle type polycarboxylic acid collapse-preventing agent is 0.02% to 0.2% of the total gelling material mass.